Thermal transport through carbon nanotubes based nanofluid flow over a rotating cylinder with statistical analysis for heat transfer rate - Yijie Li; Yuchi Leng; Mahnoor Sarfraz; Nevine M. Gunaime; Jawad Ahmed; Ahmed M. Hassan; Mohamed Abdelghany Elkotb (Case Studies in Thermal Engineering, 2023)
This study investigates the impact of magnetohydrodynamic effects and thermal radiation on axisymmetric flow with carbon nanotubes over a rotating cylinder. The thermal energy behavior of the nanofluid is analyzed using the Xue model, with water as the base fluid and two different types of nanoparticles: single-walled carbon nanotubes (SWCNTs) and multi-walled carbon nanotubes (MWCNTs). The governing flow problem is transformed through appropriate transformations, resulting in a system of ordinary differential equations. Numerical solutions are obtained using the bvp4c function in MATLAB. The results indicate that the thermal transport coefficient increases with the radiation number in both SWCNTs and MWCNTs cases. Further, the presence of nanoparticles in the nanofluid leads to an increase in the thermal transport coefficient due to the volume fraction of the nanoparticles. Moreover, the study reveals that water-based MWCNTs exhibit a higher heat transfer rate than water-based SWCNTs. These findings contribute to understanding thermal energy characteristics in nanofluids and have implications for applications such as heat exchangers, electronic cooling systems, and the thermal management of advanced materials.